Tecendo relações: a feira da agricultura familiar como espaço para além da comercialização de alimentos - Cavali , Ana Paula (2018)
This paper goal is to analyze and understand the relationships of sociabilities existing among the actors of family agriculture fairs in the municipalities of Marechal Cândido Rondon and Medianeira. These municipalities are in the western region of Paraná, considered the largest soybean producer in the state. The main topic in this research is the relationship between farmers and consumers in relation to the marketing process, but also to the various other possible interactions. We have chosen an essentially qualitative research of ethnographic approach, using the semistructured interview, observation, photographic records and the field notebook. Through the speeches, we observe that the fair visitors are attracted not only by the choice of healthier, fresh, a reliable source of food, but also because the fair space provides them with important relationships and interactions with farmers, and with other regulars. We work the results and discussions in three categories, namely: family farming (productivity, marketing), ruralities and food security and sustainability. In these categories a brief synthesis is made on the subject intertwined with the speeches of the interlocutors in order to promote dialogue with the theory. In the words of the farmers, the significance of the fairs became clear, not only as an important source of income. They are also aware of their responsibility as regards culture and food security. It is clear that, the act of "doing the fair" has been fitting in the routine of these people, because in this space they recover important values, knowledge, memories, perceptions that are not raised in the purchases made in the big supermarkets. It is important that the fairs continue to have their reproductive space preserved, above all, due to the social transformations in the alimentary practices in the process of alimentary modernity. They provide relationships of sociability and trust uncommon in the marketing process, in addition, it guarantees considerable autonomy to farmers. In this context, fairs can be considered as places of resistance and still play an admirable role in the food supply for the urban population. In addition, it facilitates reliability relationships in the exchange process carried out, to the point where the consumer becomes "a customer", which differs from that buyer who is sporadic.